Modelo para la interpretación del territorio. Parámetros y patrones en el uso del espacio urbano - Hernández Bolaños, Bernardino (Universidad Michoacana de San Nicolás de Hidalgo, 2017)
In this work, is presented a model designed to interpret with its own parameters, the intensity of the influence of a social phenomenon on the urban space. For the study of territory, conventional data collection techniques and methods were implemented, interrelated with different forms of perception to generate new urban interpretations conducive to the understanding of social trends and their materialization in the built space. The territory became a field of observation, research and analysis generating results related to the dynamics of society and being a descriptor of an urban history progressively influenced by behavior patterns. This work reversed the current tendency to consider the urban space only as a field of intervention and application of economic, sociological or urban models, to become now a field generating information... The detailed systematization of the model was applied to the city of Tzintzuntzan, Michoacán, locality of a scale attainable for the design pretensions and with the presence of a strong migratory phenomenon considered for the case study, as a social phenomenon. Reading the structure of the model will facilitate the understanding of the city as a complex system resulting from various human activities forged in the quest to meet individual and collective needs in a space and a given time. The city is a platform in which its people are mobilized to survive and to develop emotionally and intellectually ... the city is the physical resultant of a human intentionality. The results of the model-integrated in an indicator called the Index of Interpretation of Parameters and Patterns (IIPP) - allow the spatialization of the results of this intentionality by reference units (city blocks). They allow us to understand the human dynamics, the morphological evolution of the locality and the emergence of sites and centralities that -in a reactive way to the social force exerted- are presented in urban spaces turned into detonators of new activities and new growth. The study of the components and the linear correlation of the results of the model, will allow a posteriori urban intervention more precise and close to the attention that the population demands.

En este trabajo profesional se presenta un modelo diseñado para interpretar con parámetros propios, la intensidad de la influencia de un fenómeno social sobre el espacio urbano. Para el estudio del territorio se implementaron técnicas y métodos convencionales de levantamiento de datos, interrelacionados con formas diferentes de percepción para generar nuevas interpretaciones urbanas conducentes a la comprensión de las tendencias sociales y su materialización en el espacio construido. El territorio se convirtió en un campo de observación, investigación y análisis generador de resultados relativos a la dinámica de la sociedad y siendo testigo descriptor de una historia urbana progresivamente influenciada por los patrones de conducta. Este trabajo invirtió la tendencia actual de considerar al espacio urbano únicamente como campo de intervención y de aplicación de modelos económicos, sociológicos o urbanos, para convertirse ahora en un campo generador de información… La sistematización a detalle del modelo se aplicó a la ciudad de Tzintzuntzan, Michoacán, localidad que presenta un fuerte fenómeno migratorio, considerado para el estudio de caso, como un fenómeno social. La lectura de la estructura del modelo facilitará la comprensión de la ciudad como un sistema complejo resultante de diversas actividades humanas forjadas en la búsqueda de satisfacer las necesidades individuales y colectivas en un espacio y un tiempo determinado. La ciudad es una plataforma en la cual su gente se moviliza para sobrevivir y para desarrollarse emocional e intelectualmente… la ciudad es la resultante física de una intencionalidad humana. Los resultados del modelo–integrados en un indicador denominado Índice de Interpretación de Parámetros y Patrones (IIPP)- permiten territorializar por unidades de referencia (manzanas de la ciudad) los resultados de esa intencionalidad. Permiten entender las dinámicas humanas, la evolución morfológica de la localidad y la emergencia de sitios y centralidades que de manera reactiva a la fuerza social ejercida- se presentan en espacios urbanos convertidos en detonadores de nuevas actividades y nuevos crecimientos.
Facultad de Arquitectura. Maestría en diseño avanzado
Keywords: info:eu-repo/classification/cti/4; FA-M-2017-0068; Espacio urbano; Sistema complejo; Fenómeno social; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/1601